VOLUME ANALYSIS OF NORMALIZATION OF THE TELUK DALAM RIVER IN BANJARMASIN CITY USING HEC-RAS SOFTWARE - Khair, Antung Akhmad Ridhani; Nashrullah, Eddy; Novitasari, Novitasari (Universitas Lambung Mangkurat, 2026)
Teluk Dalam River in Banjarmasin City has a boundary line of less than 5 meters. This causes people to have direct contact with the river, which makes it easy to dispose of waste that will cause sedimentation. Floods can occur at any time with shallowing of the channel, narrowing of the river dimensions, and the increasing population which results in reduced water catchment areas coupled with high rainfall intensity. HEC-RAS 6.5 software will simulate overflows in the river with return periods of 2, 5, 10, and 25 years. Calculation of planned rainfall using the Log Person III distribution method using rainfall data from the Syamsudin Noor Banjarmasin Class II Meteorological Station, rainfall intensity using the mononobe method, and calculation of planned discharge using the rational method. After simulation using HEC-RAS software between the planned discharge of the return period and the existing cross-section, overflows occur at every return period along the river. Normalization is needed so that the planned discharge of the return period can flow without endangering the surrounding environment. A normalization simulation was carried out in the form of changing the cross-section dimensions by increasing the depth of the river so that a dredging volume of 24,708 m3 was obtained.Keywords: Normalization, Flood, HEC-RAS, Unsteady Flow, Teluk Dalam River